Experimental Study on Influence of Connection Defects on Joint Strength of Half-Grouted Sleeve Splicing of Rebar - Hong Guo; Jiaxin Zhang; Changwei Wang (Advances in Civil Engineering)
The different types of defects of half grouting sleeves will remarkably increase the risks of precast concrete structures. In order to better understand the defects of rebar connections between half grouting sleeves, six different test groups on insufficient grout height, insufficient compactness, rebar offset, insufficient rebar anchor length, overtime grouting, and control group had been researched. The uniaxial tension experiments were conducted for the 24 different specimens, and load-slip curves were also analyzed. The results of the experiments showed that the outside of the rebar was snapped off as for the destruction mode, while the destruction mode changed as the increment of the degree of defect surpasses the critical value. The bearing capacity and deformability were dropped with the increase in the degree of defects, and a critical value of rebar anchoring length of sleeve was discovered. In the end, different finite-element models were built based on different deficient situations, and load-slip constitutive model was obtained, which would be helpful to evaluate the structural performance of precast concrete structures in construction.